Magnesium status modulating the effect of serum vitamin D levels on retinopathy: National Health and Nutrition Examination Survey 2005 to 2008 - Xu, Lei; Yuan, Penghua; Liu, Wanrong; Liu, Linlin; Li, Xiongfeng; Xie, Lianfeng (Frontiers in Nutrition, 2024)
Aim Magnesium levels may influence the effect of vitamin D levels on the body. This study aimed to assess the combined effect of magnesium status as reflected by magnesium depletion score (MDS) and vitamin D status on the risk of retinopathy. Methods This cross-sectional study included participants aged 40 years and older with complete information on vitamin D, MDS, and retinopathy assessment from the 2005–2008 National Health and Nutrition Examination Survey (NHANES). Logistic regression analysis was utilized to analyze the relationship of MDS and vitamin D with retinopathy and expressed as odds ratio (OR) and 95% confidence interval (CI). Results Of these 4,953 participants included, 602 (9.53%) participants had retinopathy. Serum vitamin D levels ≤30 nmol/L (vs. >30 nmol/L) (OR = 1.38, 95%CI: 1.05–1.81) and MDS >2 points (vs. ≤2 points) (OR = 1.47, 95%CI: 1.01–2.16) were associated with higher odds of retinopathy. There was an interaction between MDS and vitamin D on the increased odds of retinopathy (OR = 2.29, 95%CI: 1.12–4.68, Pinteraction = 0.025). In different MDS groups, serum vitamin D levels ≤30 nmol/L increased the odds of retinopathy only in the MDS >2 group (OR = 2.90, 95%CI: 1.16–7.24), but not in the MDS ≤2 group (p = 0.293). Subgroups analyses demonstrated that the interaction between MDS and serum vitamin D on retinopathy was observed in males (OR = 6.88, 95%CI: 1.41–33.66, Pinteraction = 0.019), people with diabetes (OR = 3.43, 95%CI: 1.78–6.63, Pinteraction < 0.001), and people with body mass index (BMI) ≥25 kg/m2 (OR = 2.46, 95%CI: 1.11–5.44, Pinteraction = 0.028). Conclusion Magnesium plays a moderating role in the relationship between serum vitamin D and retinopathy. The protective effect of vitamin D against retinopathy was primarily present among those with inadequate magnesium levels.